Transcription factors regulating the specification of brainstem respiratory neurons - Xia, Yiling; Cui, Ke; Alonso, Antonia; Lowenstein, Elijah D.; Hernandez-Miranda, Luis R. (Frontiers in Molecular Neuroscience, 2022)
Breathing (or respiration) is an unconscious and complex motor behavior which neuronal drive emerges from the brainstem. In simplistic terms, respiratory motor activity comprises two phases, inspiration (uptake of oxygen, O2) and expiration (release of carbon dioxide, CO2). Breathing is not rigid, but instead highly adaptable to external and internal physiological demands of the organism. The neurons that generate, monitor, and adjust breathing patterns locate to two major brainstem structures, the pons and medulla oblongata. Extensive research over the last three decades has begun to identify the developmental origins of most brainstem neurons that control different aspects of breathing. This research has also elucidated the transcriptional control that secures the specification of brainstem respiratory neurons. In this review, we aim to summarize our current knowledge on the transcriptional regulation that operates during the specification of respiratory neurons, and we will highlight the cell lineages that contribute to the central respiratory circuit. Lastly, we will discuss on genetic disturbances altering transcription factor regulation and their impact in hypoventilation disorders in humans.